Enhancing Guest Engagement through Sustainable Practices: The Role of Lobby Ambassadors at The Apurva Kempinski Bali, Indonesia - Budiartini , Ni Kadek Rini; Suarja, I Ketut; Nadra, Nyoman Mastiani; Suja, I Ketut; Armoni, Ni Luh Eka; Chaerunnisah , Indah Utami; Utama, I Gusti Bagus Rai (Technium Business and Management, 2024)
The research titled " Enhancing Guest Engagement through Sustainable Practices: The Role of Lobby Ambassadors at The Apurva Kempinski Bali, Indonesia " investigates the sustainable products offered by The Apurva Kempinski Bali and their effectiveness in attracting guests. This quantitative descriptive study utilized a questionnaire as its primary research instrument, targeting guests of the hotel, with a sample size of 70 participants. The analysis was conducted using various statistical tools, including descriptive analysis, classical assumption tests, simple linear regression analysis, validity and reliability tests, coefficient of determination tests, and T-tests via SPSS version 25. The findings indicate that sustainable products play a crucial role in enhancing guest interest in visiting The Apurva Kempinski Bali. The implementation of these products has been executed effectively. In the context of globalization, it is essential for tourism businesses to prioritize not only profitability but also their environmental impact. The Lobby Ambassador serves as a vital link between the hotel and its guests, effectively communicating the sustainable initiatives of The Apurva Kempinski Bali. Given their frequent interactions with guests, Lobby Ambassadors are positioned to educate visitors about the hotel's sustainable offerings. This study highlights the importance of sustainability in the hospitality sector, aligning with contemporary consumer preferences for environmentally responsible practices. As travelers increasingly seek eco-friendly options, hotels that successfully integrate sustainability into their operations can enhance guest satisfaction and loyalty. Thus, the role of the Lobby Ambassador is not only significant in promoting sustainable products but also instrumental in fostering a deeper understanding among guests regarding their benefits, ultimately contributing to a more sustainable tourism experience.